Natural surfactants for pharmaceutical emulsion - Hadi, J. N.; Mohd Hassan, Norazian; Ahmad, Kausar (IIUM Press, 2011)
Surfactants are widely used in the preparation of pharmaceuticals. In emulsion, it is a vital ingredient that allows mixing of two immiscible liquids. Emulsions have significant importance as carriers for water-insoluble drugs. There are many types of synthetic surfactants but there are also known natural surfactants which have been used and more to be explored.